2008
DOI: 10.1086/592999
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Viviparity‐Driven‐Conflict Hypothesis: Parent‐Offspring Conflict and the Evolution of Reproductive Isolation in a Poeciliid Fish

Abstract: The evolution of viviparity increases the potential for genomic conflicts between mothers and offspring over the level of maternal investment. The viviparity-driven-conflict hypothesis predicts that such conflicts will drive the evolution of asymmetrical reproductive isolation between populations with divergent mating systems. We tested this hypothesis using crosses between populations of a poeciliid fish that differ in their level of polyandry. Our results support the prediction of an asymmetry in the rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 60 publications
6
56
1
Order By: Relevance
“…In two previous studies, we observed isolation asymmetry in RHCs between populations of least killifish (Heterandria formosa) that display differences in size at birth [5,6]. In both of these studies, crosses between a female from a population characterized by small offspring (SO populations) and a male from a population characterized by large offspring (LO populations) had a higher rate of aborted embryos than the reciprocal hybrid cross.…”
Section: Introductionmentioning
confidence: 87%
“…In two previous studies, we observed isolation asymmetry in RHCs between populations of least killifish (Heterandria formosa) that display differences in size at birth [5,6]. In both of these studies, crosses between a female from a population characterized by small offspring (SO populations) and a male from a population characterized by large offspring (LO populations) had a higher rate of aborted embryos than the reciprocal hybrid cross.…”
Section: Introductionmentioning
confidence: 87%
“…These aborted seeds may potentially grow rapidly because micropylar peripheral and chalazal endosperms are the tissues, where resources are transferred from endosperm to embryo and from the mother tissues to an endosperm, respectively. In a viviparous fish, high rates of offspring abortion are observed but surviving offspring are large if females are from a relatively monandrous population (where females inhibit the demand of offspring weakly) are crossed with males from a relatively polyandrous population (where offspring demands resources strongly) than if those females are crossed with males from the same monandrous population (Schrader and Travis, 2008). This result also suggests that the cost of overgrowth exists.…”
Section: Modelmentioning
confidence: 93%
“…The costs of overgrowth may exist in many organisms, including plants and animals (Carputo et al, 1999;Costa et al, 2004;Dawson, 1965;Haig and Westoby, 1991;Schrader and Travis, 2008;Scott et al, 1998;Vinkenoog et al, 2003). In plants, the balance of genomes in an endosperm is critical for normal seed maturation, and genomic imbalance often results in abortion of developing seeds (Carputo et al, 1999;Costa et al, 2004;Haig and Westoby, 1991;Scott et al, 1998;Vinkenoog et al, 2003).…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Poeciliids have been widely used for studying in fields ranging from ecology, evolution, genetics, and genomics to systematics. Species in the family Poeciliidae have been investigated in order to improve our understanding of the evolution of several life-history and behavioral traits (Kang et al, 2013;Schrader & Travis, 2008, 2009). Monterrey platyfish is also a small ornamental fish.…”
mentioning
confidence: 99%